Analysis of Capital Structure and Financial Performance on Firm Value : Systematic Literature Review - Nugraha, Aditya Surya (IJBLE Scientific Publications Community Inc., 2025)
This study aims to consider financial services in terms of company values ​​and capital structure. This study used external secondary data received by Google Scholar from 2019-2024, followed by a systematic literature overview (SLR). Based on the results of our analysis of the findings of our research, we conclude that financial services have a significant impact on the value of a company. Furthermore, capital structures have a positive and important effect on the value of a company. If the company's performance can optimize the company's value, the company's goals are achieved